The potential to breed a low‐protein maize for protein‐restricted diets. Issue 6 (19th September 2021) - Woore, Matthew S.; Flint‐Garcia, Sherry A.; Holland, James B.
Abstract: Inborn errors of amino acid metabolism, such as phenylketonuria (PKU), are human genetic conditions that result in an inability to metabolize certain amino acids, requiring lifelong maintenance of a very restrictive low‐protein diet. In the case of PKU, this diet does not permit consumption of most maize ( Zea mays L.) products, yet maize is a major part of the human diet and is especially significant in some cultures. Kernel protein content, and to a lesser extent amino acid composition, is variable in maize. Breeding maize for low kernel protein content or low amounts of specific amino acids such as phenylalanine might expand the restrictive diets and improve quality of life for people with amino acid metabolic disorders. To test the potential of breeding low‐protein‐content maize, diverse samples of hybrid or open‐pollinated cultivars and inbreds were evaluated across two locations in two years for grain protein content and amino acid composition. Consistent with previous reports, kernel protein content varied widely across maize varieties and is highly heritable in the broad sense. We found that phenylalanine content (as a proportion of grain weight) and phenylalanine composition (as a proportion of total protein) are also highly heritable in the broad sense. As previously reported, reasonably accurate estimation of protein content is possible with near‐infrared spectrophotometry, whereas measuring phenylalanine content requires a destructive, costly, and time‐consuming laboratory analysis. Because phenylalanine content was strongly correlated with total kernel protein, breeding primarily aimed at reducing grain protein content should permit efficient selection of maize cultivars sufficiently low in phenylalanine to permit broader inclusion in the PKU diet. Core Ideas: Maize with low protein or low phenylalanine contents could be used in metabolic disorder diets. The proportion of maize grain protein due to phenylalanine does not vary much. Total protein content varies considerably among maize varieties and can be measured easily. We propose selection for low‐protein grain for use in metabolic disorder diets.